1966
DOI: 10.1111/j.2044-8295.1966.tb01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Set and the Generalization of Perceptual Defence

Abstract: The present paper takes as its starting point the view that the apparent generalization of perceptual defence is to be attributed to an interruption of the observer's set. Two possibilities with regard to the nature of this set are examined, and the experimental results clearly support one of them: the view that ‘a set to see neutral words' is operative. Difficulties in understanding this formulation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1971
1971
1971
1971

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The data from this experiment support the view that perceptual defense does occur, and cast doubt upon the hypothesis that set disruption can account for previous data that suggest the presence of a perceptual defense mechanism. The demonstration by Forrest, et al (1966) that a similar reaction occurs with nonsense words suggests that an avoidance response need not be postulated to explain this phenomenon. The process by which the defense reaction operates has yet to be determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from this experiment support the view that perceptual defense does occur, and cast doubt upon the hypothesis that set disruption can account for previous data that suggest the presence of a perceptual defense mechanism. The demonstration by Forrest, et al (1966) that a similar reaction occurs with nonsense words suggests that an avoidance response need not be postulated to explain this phenomenon. The process by which the defense reaction operates has yet to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…However, Forrest, Gordon, and Taylor (1965) have demonstrated that evidence supporting this hypothesis may be due to a disruption of set rather than to a defense mechanism. Taylor and Forrest (1966) provide data which suggest that we have a set to see neutral, as opposed to taboo, words.…”
mentioning
confidence: 97%